1994
DOI: 10.1002/gcc.2870100211
|View full text |Cite
|
Sign up to set email alerts
|

TP53 alterations and clinical outcome in low grade astrocytomas

Abstract: Thirty-eight WHO grade II astrocytomas and 10 malignant recurrent gliomas in these patients were examined for the presence of TP53 alterations. Seventeen/38 low grade astrocytomas and 6/10 malignant recurrent tumors harbored mutations of the gene detected by SSCP analysis and direct sequencing of PCR products. TP53 mutations in five out of six high grade mutant tumors were already present in the corresponding low grade astrocytomas. In two cases, TP53 mutations present in the low grade astrocytoma could not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…A trend to poor outcome had been previously observed in patients with p53 immunopositive astrocytic tumors without reaching statistical signi®cance (al Sarraj and Bridges, 1995; Chozick et al, 1994; Iuzzolino et al, 1994;Kyritsis et al, 1995), and others have found no dierence (Kraus et al, 1994). These studies are limited by the inaccuracy of immunohistochemistry in the determination of p53 status (Hall and Lane, 1994).…”
Section: Relationship Between Tp53 Status and Outcomementioning
confidence: 89%
“…A trend to poor outcome had been previously observed in patients with p53 immunopositive astrocytic tumors without reaching statistical signi®cance (al Sarraj and Bridges, 1995; Chozick et al, 1994; Iuzzolino et al, 1994;Kyritsis et al, 1995), and others have found no dierence (Kraus et al, 1994). These studies are limited by the inaccuracy of immunohistochemistry in the determination of p53 status (Hall and Lane, 1994).…”
Section: Relationship Between Tp53 Status and Outcomementioning
confidence: 89%
“…2,31 Several workers have used proliferation index and p53 gene alterations for prediction of recurrence but results are controversial. 5,8,9,13,15,17,19,24,25,29 Similarly, the relationship between malignant progression and apoptosis is not clearly defined. 3,5,7,24,27 Nakamura et al 24 studied p53 protein expression, MIB-1 labeling index (MIB-1 LI) and apoptotic index (AI) in 46 recurrent anaplastic astrocytomas and reported that MIB-1 LI and AI were higher in the recurrent compared to the initial tumor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic significance of p53 mutations in LGAs is unclear, with some studies showing it to be associated with malignant progression and shorter progressionfree and overall survival while others have not seen any significant association. 1,6,9,11,15,16 More recently, it has been shown that gemistocytic astrocytomas have a higher number of microglia, with more microglia being present when the fraction of gemistocytes is high. 8 Additionally gemistocytes were seen to be reactive for major histocompatibility complex Class II molecules.…”
mentioning
confidence: 99%